Dietary interventions to prevent high-fructose diet–associated worsening of colitis and colitis-associated tumorigenesis in mice. (22nd March 2021) - Nishiguchi, Ryohei; Basu, Srijani; Staab, Hannah A; Ito, Naotake; Zhou, Xi Kathy; Wang, Hanhan; Ha, Taehoon; Johncilla, Melanie; Yantiss, Rhonda K; Montrose, David C; Dannenberg, Andrew J
Abstract: Diet is believed to be an important factor in the pathogenesis of inflammatory bowel disease. High consumption of dietary fructose has been shown to exacerbate experimental colitis, an effect mediated through the gut microbiota. This study evaluated whether dietary alterations could attenuate the detrimental effects of a high-fructose diet (HFrD) in experimental colitis. First, we determined whether the procolitic effects of a HFrD could be reversed by switching mice from a HFrD to a control diet. This diet change completely prevented HFrD-induced worsening of acute colitis, in association with a rapid normalization of the microbiota. Second, we tested the effects of dietary fiber, which demonstrated that psyllium was the most effective type of fiber for protecting against HFrD-induced worsening of acute colitis, compared with pectin, inulin, or cellulose. In fact, supplemental psyllium nearly completely prevented the detrimental effects of the HFrD, an effect associated with a shift in the gut microbiota. We next determined whether the protective effects of these interventions could be extended to chronic colitis and colitis-associated tumorigenesis. Using the azoxymethane/dextran sodium sulfate model, we first demonstrated that HFrD feeding exacerbated chronic colitis and increased colitis-associated tumorigenesis. Using the same dietary changes tested in the acute colitis setting, we also showed that mice were protected from HFrD-mediated enhanced chronic colitis and tumorigenesis, upon either diet switching or psyllium supplementation. Taken together, these findings suggest that high consumption of fructose may enhance colon tumorigenesis associated with long-standing colitis, an effect that could be reduced by dietary alterations. Abstract : Switching from a high-fructose diet to a control diet or treatment with psyllium fiber protected against the procolitic effects of dietary fructose. These interventions also suppressed high-fructose diet–mediated increase in colitis-associated colorectal tumorigenesis.